Asymmetric power in Malaysian politics : Muhyiddin’s domination - Tunku Nashril-Abaidah; Mohammad Agus Yusoff (Penerbit Universiti Kebangsaan Malaysia, 2022)
Muhyiddin’s appointment as Malaysia’s prime minister in February 2020 came as a surprise to many. What is even more surprising is that he was able to defend his position despite having a dubious majority. His ability to dominate politics is something that needs to be explored. This article unfolds the factors of this domination and provides a theoretical explanation. It argues that the asymmetrical power stipulated by the constitution resulted in the domination of the prime minister in Malaysia, thus creating an imbalance of power for the prime minister to be the dominant political actor. Although Muhyiddin was seen as a weak political player, his position as prime minister has allowed him to dominate the political process and centralise his powers from the nature of asymmetrical power. This article is qualitative in nature and uses interview as the main data collection method. This paper concludes that the prime minister will forever be the dominant actor if centralisation becomes the fundamental governing element.